THE EFFECT OF HEALTH PROMOTION USING LEAFLETS AND AUDIO-VISUAL ON IMPROVING KNOWLEDGE AND ATTITUDE TOWARD THE DANGER OF HIV/AIDS AMONG ADOLESCENTS - yafrinal - siregar; Kintoko Rochadi; Namora Lubis (International Journal of Nursing and Health Services (IJNHS), 2019)
HIV/AIDS in adolescents cannot be separated from globalization development, which causes their current social changes and negative lifestyle such as pre-marriage sex, keeping on changing sex partners, and drug abuse. Promotional action should be done to prevent from HIV/ASIDS in adolescents by using leaflet and audio-visual media, which provide information and education about the danger of HIV/AIDS so that they will have good knowledge and positive attitude. The research problem was how about the influence of promotion media using leaflets and audio-visual on adolescents' knowledge and attitude, The objective of the research was to analyze the influence of promotion media using leaflets and audio-visual on adolescents' knowledge and attitude toward the danger of HIV/AIDS at SMK Swasta Imelda, Medan. Using the Wilcoxon test tested the hypothesis. The result of the research showed that there was significant influence of leaflet and audio-visual media (p<0.05) on adolescents' knowledge and attitude in the post intervention. The conclusion was that leaflet and audio-visual media were more effective in increasing adolescents' knowledge and attitude toward the danger of HIV/AIDS. It is recommended that parents control democratically their children at home or outside their homes. The school management should increase the cooperation with parents in order to increase students' academic development, and the health care providers in the neighborhood should increase health education program. Keywords: Leaflet, Audio-Visual, Knowledge, Attitude, Danger of HIV/AIDS